Formation of Religious Character in Santri Students at the Abu Dzar Al Ghifari Islamic Boarding School Malang - Yunyanto, Rezza Dwiyoga; Khozin, Khozin; Rahim, Fathor (Universitas Muhammadiyah Magelang, 2021)
Limited time in studying religious material is one of the factors of student delinquency in class. Student Islamic boarding schools can be used as a deepening of religious material to the aim that they can form a religious character. This study aims to determine the process and reasons for the formation of religious character among non-religious students at the Abu Dzar Al Ghifari Islamic Boarding School Malang. This research method uses a qualitative approach and type of case study research. Researchers conducted in-depth interviews, participatory observation and collected documentation as data diggers. From this study, it was found that the formation of religious character in pesantren student was carried out in various activities, both daily, weekly and incidental in nature. Meanwhile, the method used in the formation of religious character is the method of advice, exemplary and habituation. Also, this religious character building is to create Muslim plus characters among students. The Abu Dzar Al Ghifari Student Islamic Boarding School in Malang can be the right place for students majoring in non-religion to form their religious character.